Group A Î²-hemolytic Streptococcus Detection Using Anti-Outer Membrane Protein (OMP) Immunoglobulin G (IgG) - Hamid Hunaif Dhofi Alluza; Ema Dianita Mayasari; Sumarno Reto Prawiro; Sri Winarsih (Journal of Tropical Life Science, 2017)
Streptococcal pharyngitis sequel such as Rheumatic Fever (RF) or Rheumatic Heart Disease (RHD) is an autoimmune response mediated by T cells and IgG. Since it is an autoimmune process, the result of bacterial culture as the gold standard of diagnosis often shows negative results. IgG against the 33 kDa OMP is considered as an important mediator in the process of these autoimmune diseases, so its presence in blood serum can be used as a diagnostic tool. The purpose of this study is to prove that 33 kDa OMP is one of the immunogenic parts of the Streptococcus Group A Î²-hemolytic, so it is expected that IgG anti-33 kDa OMP can recognize and respond the bacteria and to support the probability of the Streptococcus Group A Î²-hemolytic infection. This study was a laboratory experimental study with a control group design. Animal used was RattusNovergicus immunized with whole cell bacteria or 33 kDa OMP mixed with Complete Freundâ€™s Adjuvant or Incomplete Freundâ€™s Adjuvant. Polyclonal IgG was obtained by drawing blood serum from the animals after immunization with Streptococcus Group A Î²-hemolytic for 4 weeks (A; n = 5) and 8 weeks (B; n = 5) or immunization with OMP 33 kDa for 4 weeks (C; n = 5) and 8 weeks (D; n = 5) and also negative control group (E; n = 5). Immunological tests were done using Dot Blot assay, ELISA, and immunocytochemical examination. The data obtained was then evaluated with statistical tests Kruskal-Wallis, Mann-Whitney and Repeated ANOVA (p < 0.05). The result showed that there was a difference in humoral immune response (IgG) between the groups albeit the difference was not significant (p > 0.05). Dot Blot and immunocytochemical tests indicated that IgG anti-33 kDa OMP were able to recognize and respond the Streptococcus Group A Î²-hemolytic antigen. This study concluded that 33 kDa OMP was the immunogenic part of the bacteria and that IgG anti-33 kDa OMP could recognize and respond the Streptococcus Group A Î²-hemolytic bacteria.Â